10. PRIMORDIALISME DALAM HUBUNGAN TRANSNASIONAL: PERAN IDENTITAS DALAM MENDORONG ARUS PENGUNGSI SURIAH KE LEBANON, 2011 – 2014 - Pratama, Ramaditya Anugrah; Utomo, Tri Cahyo; Rosyidin, Mohammad (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2016)
This research aims to determine why the Syrian refugees choose to seek shelters inLebanon and to analyze the role of identity on their influx to Lebanon. Lebanon hasbecome the second largest refugee host country in the world, receiving nearly 1,2 millionrefugees as of 2014. In fact, Lebanon is a country with a limited economic capabilitiescompounded by sectarian conflict, resource scarcity, and a political instability. From aconstructivist approaches, this researches argues that there are non-strategic considerationsthat underlines the refugees' decision to travel across border to Lebanon, particularly thepresence of kinship, brotherhood, and common identities which underlies the openness forrefugees and a positive reception from the Lebanese people. Those primordial ties led to acollaborative, integrative, and positive relations between people from two countries. Thisresearch further proves a constructivist assumption that in transnational relations is notmerely driven by a rational considerations, but also in a non-rational aspect in thisparticular case, under the basis of primordial ties.